Normalizing Abusive Language on Social Media: Prevention Strategies and Islamic Education Approaches - Iswandi Iswandi; Taufik Hidayat; Sar'an (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2026)
The development of social media has significantly changed people's communication patterns, but at the same time, it has given rise to issues of language ethics, particularly the widespread use of offensive language, which has undergone a process of normalization. Abusive language is no longer viewed as a violation but rather as part of a normal digital communication culture, particularly among children and adolescents. This phenomenon has the potential to influence character formation, reduce politeness, and weaken social empathy. This study aims to analyze the normalization of offensive language on social media, identify influencing factors, and examine prevention strategies through an Islamic education approach. This research used a qualitative approach with a case study approach. The subjects consisted of adolescents who actively use social media, their parents, and Islamic Religious Education teachers. Data were collected through in-depth observation of social media activity, semi-structured interviews, and documentation studies. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing, applying triangulation of sources and methods to ensure data validity. The results indicate that the normalization of offensive language occurs through repeated exposure, digital social pressure, and minimal guidance on language ethics from families and schools. Harsh language normalized in digital spaces carries over into everyday social interactions. However, Islamic education has proven to play a strategic role in preventing this phenomenon through internalizing the values ​​of language etiquette, leading by example, and strengthening noble morals. This research emphasizes the importance of integrating Islamic education into digital literacy to foster a culture of polite and responsible communication on social media.